Montenegro : Overview of Tobacco Use, Tobacco Control Legislation and Taxation - World Bank Group (World Bank, Washington, DC, 2019)
Montenegro became a Party to the WHO Framework Convention on Tobacco Control in 2006 and ratified the Protocol to Eliminate Illicit Trade in Tobacco Products in 2017. Tobacco excise hikes, undertaken in Montenegro in 2009-2011, were successful both in fiscal and public health terms. Revenues from tobacco excises rose from about 4 million in 2007 to 44 million euro in 2011. Annual cigarette sales declined from more than 1.5 billion cigarettes in 2008-2011 to less than 1 billion cigarettes in 2014 and further years. However, in 2013-2016, tobacco excise increases were too small to reduce tobacco affordability and tobacco sales, and tobacco revenues did not change much. In August 2017, Montenegro adopted an ambitious plan of excise tax increases; however, the tobacco industry responded with series of hidden actions (forestalling and price over-shifting) which temporarily reduced tobacco excise revenue in early 2018. As the next high increase of excise rate was scheduled for January 2018, and at the same time, VAT rate increased from 19 to 21, the industry substantially increased cigarette supply in the second half of 2017 and sharply reduced it in early 2018 as it already had in stocks large numbers of cigarettes for which excise was paid in 2017. The excise revenue substantially increased in late 2017, but declined in early 2018 despite the excise rate increase. The industry organized the media campaign to persuade the government that this revenue decline was allegedly caused by tax-driven growth in cigarette smuggling (while no rigorous evidence of such growth was presented), and the only way to fight smuggling is the reduction of cigarette excise. From September 2018, the excise rates were reduced, while they are still higher than those planned before 2017. The plan of annual tobacco excise changes until 2025 was already adopted by authorities, but the proposed changes have rather low potential to reduce the tobacco consumption and to increase government revenue. The expected total excise rate in 2025 will be below 90 euro (minimum EU level). Montenegro is able to conduct a more aggressive and successful tobacco taxation policy which can both reduce tobacco consumption and increase tobacco revenue.